Using Psyllium to Prevent and Treat Obesity Comorbidities - Pal, Sebely; Radavelli-Bagatini, S.; Ho, S.; McKay, J.; Jane, M. (Elsevier Inc., 2014)
Current evidence supports the notion that the consumption of a high-fiber diet provides benefits to many components of metabolic syndrome (MS), cardiovascular disease, and type 2 diabetes. Psyllium is one of the most widely used fiber supplements because it is reasonably cheap and is better tolerated than other fiber supplements. Psyllium supplementation reduces appetite, improves blood glucose levels and the insulin response, reduces blood pressure, and has beneficial effects on the lipid profile in both animals and humans, thereby reducing metabolic risk factors. Psyllium seems to improve body weight in animals, but its effects on body weight in humans is unresolved. Psyllium supplementation may be beneficial for patients with metabolic syndrome risk factors such as hypercholesterolemia, hypertriglyceridemia, and hyperglycemia, but its efficacy in the management of body weight, body composition, appetite, and hypertension requires further investigation. © 2014 Elsevier Inc. All rights reserved.